Hardiness Personality and Work Stress Among Female Riders: Ketangguhan, Kepribadian, dan Stres Kerja di Kalangan Penunggang Kuda Wanita - Resti Kusumawati; Widyastuti (Academia Open, 2025)
General Background: Female online motorcycle riders operate in high-risk outdoor environments characterized by demanding workloads, economic uncertainty, and minority gender status in a male-dominated occupation, conditions associated with work stress. Specific Background: Work stress encompasses physiological, psychological, and behavioral responses arising from organizational, environmental, and individual factors, while hardiness personality comprising control, commitment, and challenge represents an individual resilience characteristic relevant to occupational settings. Knowledge Gap: Empirical evidence examining the association between hardiness personality and work stress among female online motorcycle riders in Surabaya remains limited. Aims: This study aimed to determine the relationship between hardiness personality and work stress among female online motorcycle riders in Surabaya. Results: Using a quantitative correlational design with quota sampling, 100 respondents completed the Occupational Hardiness Questionnaire (r=0.760) and a Work Stress Scale (r=0.920). Data analysis with Spearman’s rho indicated a significant negative correlation (r = -0.798; p < 0.001), with hardiness personality explaining 60.7% of the variance in work stress. Most respondents demonstrated high hardiness (35%) and low work stress (31%). Novelty: This study provides empirical evidence from a gender-specific occupational group within the Indonesian gig economy, highlighting the central role of hardiness personality in relation to work stress. Implications: Strengthening control, commitment, and challenge orientations may support stress management strategies, occupational safety awareness, and sustainable work participation among female online motorcycle riders. Highlights: A Strong Inverse Correlation Was Identified Between Psychological Resilience Traits and Occupational Strain (R = -0.798; P < 0.001). The Resilience Construct Accounted for 60.7% of Variance in Job-Related Strain. Most Participants Demonstrated Elevated Resilience Levels Alongside Comparatively Low Strain Scores. Keywords: Hardiness Personality, Work Stress, Female Online Motorcycle Riders, Occupational Psychology, Surabaya